Effect of Initial Graft Tension During Anterior Talofibular Ligament Reconstruction on Ankle Kinematics, Laxity, and In Situ Forces of the Reconstructed Graft. Issue 4 (March 2020) - Sakakibara, Yuzuru; Teramoto, Atsushi; Takagi, Tetsuya; Yamakawa, Satoshi; Shoji, Hiroaki; Okada, Yohei; Kobayashi, Takuma; Kamiya, Tomoaki; Fujimiya, Mineko; Fujie, Hiromichi; Watanabe, Kota; Yamashita, Toshihiko
Background: Although a variety of surgical procedures for anterior talofibular ligament (ATFL) reconstruction have been reported, the effect of initial graft tension during ATFL reconstruction remains unclear. Purpose/Hypothesis: This study investigated the effects of initial graft tension on ATFL reconstruction. We hypothesized that a high degree of initial graft tension would cause abnormal kinematics and laxity. Study Design: Controlled laboratory study. Methods: Twelve cadaveric ankles were tested with a robotic system with 6 degrees of freedom to apply passive plantarflexion and dorsiflexion motions and a multidirectional load. A repeated measures experiment was designed with the intact ATFL, transected ATFL, and reconstructed ATFL at initial tension conditions of 10, 30, 50, and 70 N. The 3-dimensional path and reconstructed graft tension were simultaneously recorded, and the in situ forces of the ATFL and reconstructed graft were calculated with the principle of superposition. Results: Initial tension of 10 N was sufficient to imitate normal ankle kinematics and laxity, which were not significantly different when compared with those of the intact ankles. The in situ force on the reconstructed graft tended to increase as the initial tension increased. In situ force on the reconstructed graft >30 N was significantly greater than that of intact ankles. The in situ force on the ATFL was 19 N at 30° of plantarflexion. In situ forces of 21.9, 30.4, 38.2, and 46.8 N were observed at initial tensions of 10, 30, 50, and 70 N, respectively, at 30° of plantarflexion. Conclusion: Approximate ankle kinematic patterns and sufficient laxity, even with an initial tension of 10 N, could be obtained immediately after ATFL reconstruction. Moreover, excessive initial graft tension during ATFL reconstruction caused excessive in situ force on the reconstructed graft. Clinical Relevance: This study revealed the effects of initial graft tension during ATFL reconstruction. These data suggest that excessive tension during ATFL reconstruction should be avoided to ensure restoration of normal ankle motion.